The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1995
DOI: 10.1111/j.1460-9568.1995.tb01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin Excites Neostriatal Neurons in Rats via CCKA or CCKB Receptors

Abstract: The effect of iontophoretically applied cholecystokinin (CCK) on neurons of the neostriatum was studied in rats anaesthetized with urethane. The most frequently observed effect of the sulphated octapeptide (CCK-8S) on striatal neurons was excitation. Spontaneously active neurons responded more often to CCK-8S than quiescent cells. Silent, primarily non-responsive neurons could often be stimulated with CCK-8S using glutamate to induce an ongoing discharge. Thus, 45.8% of the 177 neurons studied changed their di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…We cannot discard a similar action for CCK in the glomerular circuits, insofar as the distribution of the GABAergic PG matches well with the distribution of the CCK‐containing PG in both the sensory and the synaptic subcompartments of the glomerular neuropil. Finally, CCK might exert a direct excitatory effect upon its targets, as has been reported for the striatum (Davidowa et al, 1995, 1997; Wu and Wang, 1996), hippocampus (Gronier and Debonnel, 1995), and thalamus (Cox et al, 1995). The synaptic targets of the CCK‐containing PG are the mitral and tufted cells, but, in that this peptide is released extrasynaptically, the putative targets of the action of the CCK could be any other element taking part in the glomerular circuitry and expressing CCK receptors.…”
Section: Discussionmentioning
confidence: 73%
“…We cannot discard a similar action for CCK in the glomerular circuits, insofar as the distribution of the GABAergic PG matches well with the distribution of the CCK‐containing PG in both the sensory and the synaptic subcompartments of the glomerular neuropil. Finally, CCK might exert a direct excitatory effect upon its targets, as has been reported for the striatum (Davidowa et al, 1995, 1997; Wu and Wang, 1996), hippocampus (Gronier and Debonnel, 1995), and thalamus (Cox et al, 1995). The synaptic targets of the CCK‐containing PG are the mitral and tufted cells, but, in that this peptide is released extrasynaptically, the putative targets of the action of the CCK could be any other element taking part in the glomerular circuitry and expressing CCK receptors.…”
Section: Discussionmentioning
confidence: 73%
“…The majority of electrophysiological studies have found that CCK depolarizes neurons in the peripheral nervous system (35,38,51), spinal cord (48), and brain (8,10,14,57,71,72). However, hyperpolarizing responses have also been observed in some neurons (8,38,73), and one study found that CCK augments the hyperpolarizing effects of dopamine in the ventral mesencephalon (10).…”
Section: Discussionmentioning
confidence: 99%
“…Its localisation in synaptic vesicles and release by calcium dependent mechanisms (Emson et al, 1980), together with the excitatory effects on neurones in many brain areas (e.g. Brack and Lovick, 2007;Davidowa et al, 1995;Munro et al, 1998) suggest that it functions as a neurotransmitter. CCK-8 binding sites are widely distributed throughout the rat brain, with an especially high concentration in the forebrain (Van Dijk et al, 1984).…”
Section: Cck In Neuronesmentioning
confidence: 99%